Sovereign Risk and Belief-Driven Fluctuations in the Euro Area - Corsetti, Giancarlo (IMF Working Papers; Working Paper ;, 2013)
Sovereign risk premia in several euro area countries have risen markedly since 2008, driving up credit spreads in the private sector as well. We propose a New Keynesian model of a two-region monetary union that accounts for this 'sovereign risk channel.' The model is calibrated to the euro area as of mid-2012. We show that a combination of sovereign risk in one region and strongly procyclical fiscal policy at the aggregate level exacerbates the risk of belief-driven deflationary downturns. The model provides an argument in favor of coordinated, asymmetric fiscal stances as a way to prevent selffulfilling debt crises.